Pseudoephedrine Induced Ischemic Colitis: A Case Report and Review of Literature - Muhammad Aziz; Asad Pervez; Rawish Fatima; Ajay Bansal (Case Reports in Gastrointestinal Medicine)
Ischemic colitis due to medications is common, and a number of cases have been described with pseudoephedrine as the culprit agent. We present here an interesting case of a healthy female with no risk factors who developed pseudoephedrine induced ischemic colitis. This case serves to remind the healthcare providers about the utmost importance of obtaining a comprehensive history to aid with the diagnosis.